Factors in the Formation and Development of Human Capital in the Regions of the Republic of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the essence of investing in human capital and explores the key factors influencing its formation and development. The study delves into the composition of human capital, highlighting its multifaceted nature and significance in driving economic and social progress. A central focus is placed on understanding how investments in education, healthcare, and skills development contribute to the enhancement of human capital. The analysis underscores the critical role of human capital development as a primary factor in fostering sustainable growth, innovation, and competitiveness. Through a comprehensive exploration of these elements, the article provides valuable insights into the strategic importance of prioritizing human capital investment to achieve long-term societal and economic goals.